This time it's different? Youth labour markets during "the great recession" - Niall O'Higgins (Institute for the Study of Labor (IZA), 2012)
This paper looks at the effects of the 'Great Recession' on young people's labour market experiences in the European Union. The paper documents some of the key characteristics of young people's labour market experiences during the current recession and then seeks to provide some explanations of these applying both cross-section and time series rolling regression models in order, in particular, to better understand the role of labour market institutions as a determining factor of differing experiences across countries. The analysis finds that labour market flexibility contributed significantly to the negative consequences felt by young people during the recession.
urn:nbn:de:101:1-201207125679
Keywords: I28; J13; J23; J24; 330; recession; youth labour markets; human capital; EPL; Junge Arbeitskräfte; Arbeitsmarktflexibilität; Wirtschaftskrise; Jugendarbeitslosigkeit; Arbeitnehmerschutz; EU-Staaten